Is taking gender into account for development and diffusion of agricultural innovations justified? The case of drought tolerant maize in Northern Benin - Baco, M.N.; Affoukouk, T.; Moumouni, I.; Abdoulaye, Tahirou (Academic Journals, 2015)
This study was initiated to contribute to the debate on the relationship between gender and adoption of innovations. It aims, under a participatory varietal selection, to identify the preferences of men and women farmers on maize varieties tolerant to drought in northern Benin. The methodology used is a comparison of two approaches to identify the best varieties according to gender. The first combines criteria weighting and a comparison of varieties. The second is based on the principle of democratic vote. Sixty farmers have participated in this study. The results of this work show two keys points. At the stage of criteria selection, women identified the organoleptic quality as a preferred seed characteristic. By comparing the results of the two methods of choice, it appears that both methods lead to the same results in the case of women’s preferences, while in men groups, the results vary according to the methods. It contributes to the literature by showing how distinctly women can prioritize criteria that are not the top concern of the men and by the way, can contribute to increase the adoption of varieties that contains both preferences of men and women.